2003
DOI: 10.1016/s0194-5998(03)00770-8
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 and P16 expression in recurrent nasopharyngeal carcinoma

Abstract: Background: Cyclin D1 and p16 are involved in the regulation of G1 checkpoint and may play an important role in the tumorigenesis of nasopharyngeal carcinoma (NPC). Previous studies have examined the level of expression of cyclin D1 and p16 in primary untreated NPC but no such information is available for recurrent NPC. We set out in this study to examine the expression level of cyclin D1 and p16 in recurrent NPC that have failed previous treatment with radiation +/-chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…3). Further studies showed that protein level of cyclin D1, a protein which is frequent amplifiable and altered expression in a variety of tumors including NPC (Lamb and Ewen, 2003;Lin et al, 2006), decreased markedly by metformin treatment (Fig. 4).…”
Section: Discussionmentioning
confidence: 94%
“…3). Further studies showed that protein level of cyclin D1, a protein which is frequent amplifiable and altered expression in a variety of tumors including NPC (Lamb and Ewen, 2003;Lin et al, 2006), decreased markedly by metformin treatment (Fig. 4).…”
Section: Discussionmentioning
confidence: 94%
“…The second reason could be due to the concept of "minimal residual disease" theory, which postulates that histologically undetectable tumor deposits may remain at the primary site after initial treatment; which remain biologically dormant and only manifest overt disease after a period of time. 44 It is possible that these inert cells regain dominance through acquisition of new mutations because genetic mutations among patients with recurrent NPC, such as in p16, 45 fibulin-5, 46 and FLJ10540 47 have been reported. Alternatively, recurrent cancer may acquire qualities that enhance the ability of the tumor to evade the host immune system.…”
Section: Discussionmentioning
confidence: 99%
“…44 It is possible that these inert cells regain dominance through acquisition of new mutations because genetic mutations among patients with recurrent NPC, such as in p16, 45 fibulin-5, 46 and FLJ10540 47 have been reported. Alternatively, recurrent cancer may acquire qualities that enhance the ability of the tumor to evade the host immune system.…”
mentioning
confidence: 99%
“…Some authors have reported a correlation of altered F-12 staining with worse patient outcome in lung cancer [22], although others found no such correlation [23]. Moreover, it has been reported that p16INK4a inactivation, assessed with F-12 antibody, was involved in development and progression of other malignancies such as nasopharyngeal carcinoma [24], thick melanomas [25], and adrenocortical tumours [26]. While we can not eliminate that this antibody did bind to an isoform of the human p16INK4a protein in our tests or in the previously reported studies, further investigations are required before the reported F-12 data can be attributed with certainty to the human p16INK4a protein.…”
Section: Discussionmentioning
confidence: 99%